Reward Management Strategies and Employee Satisfaction in the Colleges of Kathmandu Valley - Jitendra Prasad Upadhyay; Pitri Raj Adhikari, (Indian Journal of Management and Language (IJML), 2024)
Background: Educational institutions set up a reward management system with the hope that it makes the employees perform their activities to the satisfaction of all concerned stakeholders. However, there are many contradictions and complaints about the performance of employees in colleges, compelling the undertaking the studies. Objectives: This study aims to examine the impact of reward management strategies on employee satisfaction in colleges of Kathmandu valley. Methods: This paper uses a questionnaire survey method of 300 respondentsof different 30 colleges/campuses of Kathmandu valley and descriptive statistics and multiple regression models are used to analyze the data. Results: The beta coefficients are positive and significant for promotion, compensation, recognition, learning opportunities, and career development opportunity with employee satisfaction which indicates these variables have a positive impact on employee satisfaction. Conclusion: It is found that reward management is positively related to employee satisfaction and it is a powerful motivational factor that leads to job satisfaction. Implications: College management including universities may focus on identifying better reward management strategies to motivate the employees to enhance better productivity.